Pengaruh Iklan dan Harga di TikTok Terhadap Perilaku Konsumtif Mahasiswa Sleman Yogyakarta - Kusuma, Atika Anggraini; Pudrianisa, Sheila Lestari Giza (Persatuan Wartawan Indonesia, 2024)
The use of TikTok inspires people to shop online, especially students. With advertising and the prices given, can it influence the consumer behavior of students to purchase a product/service? The research used quantitative methods by taking samples through purpose sampling according to the specified criteria, namely 100 students in Sleman-Yogyakarta because it is famous as a student city and most campuses are located in Sleman. So it becomes the center for carrying out the largest purchasing transactions. Not surprisingly, the social mobility of students who live in Sleman is relatively high. The results of the research explain that advertising has a significant effect on consumer behavior with a calculated T of 2.034 and a T table of 1.984, meaning that the T calculated > T table value with a sig value is smaller than 0.05. Price has a significant effect on consumptive behavior with a T count of 4.327 and a T table of 1.984, meaning that the T count > T table value with a sig value is smaller than 0.05. Advertising and price have a significant effect on consumer behavior with F Calculation of 19.176 and F Table of 3.09, meaning the value of F Table>F Calculation with a sig value smaller than 0.05. The coefficient of determination is 28.3%, so the variation in consumer behavior is 71.7% determined by advertising and price variables. The AISAS theory has succeeded in explaining that human consumptive behavior is influenced by several factors, such as attention and interest in products that come from advertising and price offers, insight provided so that people will always look for them and are not even embarrassed to share information with other people. Directly, human psychology influences people's behavior in purchasing decisions. The many advertising offers and prices influence students to form consumer behavior to buy products/services repeatedly on Tiktok.